Proposal for Teacher Training Model in Steam Education - Segarra-Morales , Andrea Katalina; Juca-Aulestia, José Marcelo (Journal of Ecohumanism, 2024)
This research is developed by systematizing the literature on STEAM education in relation to skills, strategies, training, implementation and competencies. An SLR methodology is applied focused on the field of education, 46 articles were selected from the Scopus, Eric and WOS Database from the last five years, complemented with quantitative research to verify the frequency of the variables in the documentary review. The results are articulated in a design to propose a teacher training model in STEAM education, for which three dimensions are taken into consideration based on the educational actors (pre-professional, professional and expert) in order to work on the different indicators that allow a logical and systematic sequence to implement STEAM education in current educational contexts that require the development of complex competencies, mediated by emerging technologies. It is evident that teachers, from their initial training to their professional development as experts, face the challenge of preparing new generations to solve complex problems and effectively promote the development of 21st century skills, in this way, Teacher training programs contribute significantly to their professional performance, playing a crucial role in the transformation of pedagogical practice, strengthening teaching professionalism and promoting a culture of research, generating a positive impact on the quality of current education.